2015
DOI: 10.1063/1.4926423
|View full text |Cite
|
Sign up to set email alerts
|

Intersubband transitions in nonpolar GaN/Al(Ga)N heterostructures in the short- and mid-wavelength infrared regions

Abstract: This paper assesses nonpolar m-and a-plane GaN/Al(Ga)N multi-quantum-wells grown on bulk GaN for intersubband optoelectronics in the short-and mid-wavelength infrared ranges. The characterization results are compared to those for reference samples grown on the polar c-plane, and are verified by self-consistent Schrödinger-Poisson calculations. The best results in terms of mosaicity, surface roughness, photoluminescence linewidth and intensity, as well as intersubband absorption are obtained from m-plane struct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 40 publications
(52 reference statements)
1
24
0
Order By: Relevance
“…To date, promising experimental results have been reported for near-and far-infrared intersubband absorption and photodetection in m-plane nitride heterostructures utilizing limited Al-composition alloys. [2][3][4][5][6][7][8][9][10][11][12] Mid-infrared intersubband absorption in m-plane AlGaN/GaN heterostructures grown by metal-organic chemical vapor deposition (MOCVD) was demonstrated by Kotani et al [4][5][6] We reported far-infrared (THz) intersubband absorption in AlGaN/GaN superlattices grown by molecular beam epitaxy (MBE). 2 Lim et al [7][8][9][10][11] also demonstrated short-to longwavelength infrared intersubband transitions in MBE-grown AlGaN/GaN heterostructures.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…To date, promising experimental results have been reported for near-and far-infrared intersubband absorption and photodetection in m-plane nitride heterostructures utilizing limited Al-composition alloys. [2][3][4][5][6][7][8][9][10][11][12] Mid-infrared intersubband absorption in m-plane AlGaN/GaN heterostructures grown by metal-organic chemical vapor deposition (MOCVD) was demonstrated by Kotani et al [4][5][6] We reported far-infrared (THz) intersubband absorption in AlGaN/GaN superlattices grown by molecular beam epitaxy (MBE). 2 Lim et al [7][8][9][10][11] also demonstrated short-to longwavelength infrared intersubband transitions in MBE-grown AlGaN/GaN heterostructures.…”
Section: Introductionmentioning
confidence: 98%
“…Nonpolar m-plane AlGaN/GaN heterostructures are interesting from both a fundamental material growth perspective and for practical applications in infrared optoelectronic devices. [1][2][3][4][5][6][7][8][9][10][11][12] Intersubband optoelectronic devices utilize optical transitions within the conduction band of GaN/AlGaN quantum wells to emit or detect infrared radiation. The accessible wavelength range is mainly determined by the conduction band-offset between the well and the barrier material, i.e., GaN and AlGaN in this case.…”
Section: Introductionmentioning
confidence: 99%
“…The substrates were free-standing m-GaN platelets sliced from (0001)-oriented GaN boules synthesized by hydride vapor phase epitaxy (resistivity > 10 6 V Á cm, dislocation density <5 Â 10 6 cm À2 ). For each design, growth was performed under the optimum conditions for c-GaN, i.e., slightly Ga-rich conditions [10,22,23], which are known to be compatible with m-plane growth [16,24]. The GaN wells were homogeneously doped with silicon, with the doping density indicated in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that the (1-100) m-plane is the most promising nonpolar crystallographic orientation for ISB applications, based on comparative results with the (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) a-plane [16]. By adjusting the Al mole fraction in the MQWs, ISB absorption in a broad range of the infrared spectrum was demonstrated.…”
mentioning
confidence: 99%
See 1 more Smart Citation